Exosome‐delivered circRNA promotes glycolysis to induce chemoresistance through the miR‐122‐PKM2 axis in colorectal cancer. Issue 3 (24th January 2020) - Wang, Xinyi; Zhang, Haiyang; Yang, Haiou; Bai, Ming; Ning, Tao; Deng, Ting; Liu, Rui; Fan, Qian; Zhu, Kegan; Li, Jialu; Zhan, Yang; Ying, Guoguang; et al.
Abstract : Malignant tumors, including colorectal cancer (CRC), usually rely on ATP generation through aerobic glycolysis for both rapid growth and chemotherapy resistance. The M2 isoform of pyruvate kinase (PKM2) has a key role in catalyzing glycolysis, and PKM2 expression varies even within a single tumor. In this study, we confirmed that expression of PKM2 is heterogeneous in CRC cells, namely high in oxaliplatin‐resistant cells but relatively low in sensitive cells, and found that chemoresistant cells had enhanced glycolysis and ATP production. In addition, we report a PKM2‐dependent mechanism through which chemosensitive cells may gradually transform into chemoresistant cells. The circular RNA hsa_circ_0005963 (termed ciRS‐122 in this study), which was determined to be a sponge for the PKM2‐targeting miR‐122, was positively correlated with chemoresistance. In vitro and in vivo studies showed that exosomes from oxaliplatin‐resistant cells delivered ciRS‐122 to sensitive cells, thereby promoting glycolysis and drug resistance through miR‐122 sponging and PKM2 upregulation. Moreover, si‐ciRS‐122 transported by exosomes could suppress glycolysis and reverse resistance to oxaliplatin by regulating the ciRS‐122–miR‐122–PKM2 pathway in vivo . Exosomes derived from chemoresistant CRC cells could transfer ciRS‐122 across cells and promote glycolysis to reduce drug susceptibility in chemosensitive cells. This intercellular signal delivery suggests a potential novel therapeutic target and establishes a foundation for future clinical applications in drug‐resistant CRC. Abstract : Exosomes from oxaliplatin‐resistant colorectal cancer (CRC) cells transferred ciRS‐122 to oxaliplatin‐sensitive cells, enhancing glycolysis and drug resistance by promoting PKM2 expression. Furthermore, ciRS‐122 targeting through exosome‐delivered small interfering (si)RNA in vivo enhanced the drug response, indicating a novel potential approach for the reversion of oxaliplatin resistance in CRC.